2023
DOI: 10.1007/s13193-023-01779-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on Disease Progression and Postoperative Complications in Patients with Head and Neck Cancer

Abstract: The COVID-19 pandemic has created a remarkable challenge for the healthcare system. The delayed presentation, diagnosis, and treatment of head and neck cancer during the COVID-19 pandemic is expected to adversely affect outcomes. COVIDSurg collaborative group in 2020 concluded surgery ≥ 4 weeks after a positive COVID-19 swab result was associated with a lower risk of postoperative mortality. The aim of this study is to assess the disease progression due to COVID-19 infection in patients with head and neck canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(10 reference statements)
0
0
0
Order By: Relevance
“…In the head and neck region, there may be a risk of upper respiratory tract symptoms due to COVID-19 infection and associated deterioration of the general condition. In addition to the early reports of the COVID-19 pandemic [13], Koizumi et al [14] reported on the impact of the COVID-19 pandemic on the number of otolaryngological surgeries, and Nadarajan et al [15] reported on the association between surgical complications and COVID-19. Nevertheless, to the best of our knowledge, there are no reports documenting the influence of COVID-19 on managing head and neck malignancies in the inpatient setting (as per a PubMed title search employing the query "COVID-19 head and neck cancer hospitalization").…”
Section: Introductionmentioning
confidence: 99%
“…In the head and neck region, there may be a risk of upper respiratory tract symptoms due to COVID-19 infection and associated deterioration of the general condition. In addition to the early reports of the COVID-19 pandemic [13], Koizumi et al [14] reported on the impact of the COVID-19 pandemic on the number of otolaryngological surgeries, and Nadarajan et al [15] reported on the association between surgical complications and COVID-19. Nevertheless, to the best of our knowledge, there are no reports documenting the influence of COVID-19 on managing head and neck malignancies in the inpatient setting (as per a PubMed title search employing the query "COVID-19 head and neck cancer hospitalization").…”
Section: Introductionmentioning
confidence: 99%